2005
DOI: 10.1021/jm050655g
|View full text |Cite
|
Sign up to set email alerts
|

3D-QSAR Studies of Arylpyrazole Antagonists of Cannabinoid Receptor Subtypes CB1 and CB2. A Combined NMR and CoMFA Approach

Abstract: The present work focuses on the study of the three-dimensional (3D) structural requirements for selective antagonist activity of arylpyrazole compounds at the cannabinoid CB1 and CB2 receptors. Initially, a combined high-resolution two-dimensional (2D) NMR and computer modeling approach was carried out to study the solution structure of the key pyrazole derivative N-(piperidin-1-yl)-5-phenyl-1-(n-pentyl)-4-methyl-1H-pyrazole-3-carboxamide (AM263). By using the NMR-determined molecular conformers as templates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 43 publications
5
55
0
Order By: Relevance
“…The neutral antagonist analog A6a was tested in newborn mice, establishing neutral antagonism of CB1 as a component in failure-to-thrive syndrome [Fride et al, 2007]. AM263 (A7a; X5 H; Ki 5 11.1 nM), an N1 n-pentyl substituted analog of rimonabant, was examined in a three-dimensional quantitative structureactivity relationship (QSAR) study that combined nuclear magnetic resonance and comparative molecular field analysis methods [Chen et al, 2006]. The results identified (1) a requirement of a bulky substituent at N1, (2) enhanced binding due to steric and electrostatic interactions from a negatively charged bulky substituent (i.e., halogen) on the diaryl pyrazoles at the para-position of the C-5 aryl ring, (3) a disfavored CB1 binding affinity due to steric bulk at the distal region of the N-amido substituent, (4) a methyl on the pyrazole C-4 favoring high CB1 affinity and selectivity versus CB2, and (5) negatively charged groups proximal to the carbonyl oxygen favoring CB1 binding as factors for further ligand design.…”
Section: Pyrazole Core Ring Analogsmentioning
confidence: 99%
“…The neutral antagonist analog A6a was tested in newborn mice, establishing neutral antagonism of CB1 as a component in failure-to-thrive syndrome [Fride et al, 2007]. AM263 (A7a; X5 H; Ki 5 11.1 nM), an N1 n-pentyl substituted analog of rimonabant, was examined in a three-dimensional quantitative structureactivity relationship (QSAR) study that combined nuclear magnetic resonance and comparative molecular field analysis methods [Chen et al, 2006]. The results identified (1) a requirement of a bulky substituent at N1, (2) enhanced binding due to steric and electrostatic interactions from a negatively charged bulky substituent (i.e., halogen) on the diaryl pyrazoles at the para-position of the C-5 aryl ring, (3) a disfavored CB1 binding affinity due to steric bulk at the distal region of the N-amido substituent, (4) a methyl on the pyrazole C-4 favoring high CB1 affinity and selectivity versus CB2, and (5) negatively charged groups proximal to the carbonyl oxygen favoring CB1 binding as factors for further ligand design.…”
Section: Pyrazole Core Ring Analogsmentioning
confidence: 99%
“…0.6. [58] While cross-validated q 2 values are typically used to evaluate the validity of the QSAR models, few 3D QSAR models reported employ independent test sets as a measure of model performance. As Golbraikh and Tropsha [54] and Kubinyi et al [59] have shown, cross-validated q 2 values and test set r 2 values do not always correlate significantly.…”
Section: Model Validationmentioning
confidence: 99%
“…Thus, attachment of other heterocyclic moieties, which are known to possess pharmacological activity, to furan ring may lead to the fulfillment of this objective. On the other hand, pyrazole derivative are known to have significant biological and pharmacological activity [7][8][9]. As an extension of our research program aiming at the synthesis of a variety of heterocyclic systems for biological screening [10][11][12][13][14][15][16][17][18][19][20], we report here on the syntheses of some important diazospiro [4.4]nona-and tetrazaspiro [4.5]deca-2,9-diene-6-one derivatives.…”
Section: Introductionmentioning
confidence: 99%